Pengaruh Sistem Pengelolaan Dana Kas Kecil Terhadap Operasi Perusahaan Pada Pt. Pos Indonesia (Persero) Kantor Pos Lhokseumawe - Murhaban, Murhaban (PASAI, 2013)
This study aimed to determine the effect of a petty cash fund management system of the companys operations at PT Pos Indonesia (Persero) Lhokseumawe Post Office. Population and sample of the study was the post office employees Lhokseumawe by the number of questionnaires that spread 62 respondents. Regression analysis method is simple. The sampling in this study was purposive sampling method. In a data processing computer software that is used Statistical Package for Social Science (SPSS) version 16.0. The variable in this study is the independent variable management of petty cash funds (X) and the operating company(Y) is the dependent variable. Prior to hypothesis testing, which includes testing instrument validity and reliability testing. Classical assumption test the normality test, then tested the hypothesis with partial test (t test). The results showed that the correlation coefficient (R) in this study was obtained 0.694, which indicates that the degree of relationship (correlation) between the independent variables with the dependent variable of 69.4%, meaning that the companys operating variable (Y) is very closely associated with the variable fund management petty cash (X). The coefficient of determination (R2) = 0.481, meaning that 48.1% of the changes in the dependent variable (the operating company) can be explained by changes in the independent variables (management of petty cash funds). The rest, amounting to 51.9% explained by factors other variables outside of the study.